2008
DOI: 10.1300/j074v20n01_12
|View full text |Cite
|
Sign up to set email alerts
|

The Downside of Friendship: Sources of Strain in Older Women's Friendships

Abstract: This article explores sources of strain in older women's friendships. We know a fair amount about the salutary effects of women's friendships, but little about sources of strain and tension. What we do know comes from quantitative studies where subjects respond to lists, categories, or sets of exchanges, not open-ended descriptions of conflict. This project begins to fill that gap by giving voice to older women's understandings of the downside of friendship. Twenty-six older women were intensively interviewed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
0
7
0
3
Order By: Relevance
“…As idosas esperavam dos amigos o compartilhamento de interesses e hábitos pessoais semelhantes aliados à confiança, honestidade e reciprocidade, além de morar nas proximidades e possuir status social similar. Expectativas não concretizadas resultaram em tensões e sentimentos de raiva, traição, decepção, desaprovação, ciúme e tristeza (Moremen, 2008).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…As idosas esperavam dos amigos o compartilhamento de interesses e hábitos pessoais semelhantes aliados à confiança, honestidade e reciprocidade, além de morar nas proximidades e possuir status social similar. Expectativas não concretizadas resultaram em tensões e sentimentos de raiva, traição, decepção, desaprovação, ciúme e tristeza (Moremen, 2008).…”
Section: Discussionunclassified
“…Constatou-se na literatura a utilização de estratégias construtivas para a resolução de conflitos pelos idosos (Mcgraw & Walker, 2004;Birditt & Fingerman, 2005;Moremen, 2008). Em comparação aos jovens, pessoas idosas eram mais propensas a empregar a lealdade que inclui o uso de estratégias construtivas passivas frente às tensões com membros próximos de sua rede social, como por exemplo, não fazer nada e aguardar que a situação melhore para evitar aborrecer seu parceiro social.…”
Section: Discussionunclassified
“…13 In older age friendships, the disruption of expectations about how friends should be (e.g., balanced relationship) causes strain. 14 However, the harmful effects of social interventions are understudied and underestimated and specially here a gender perspective is needed.…”
Section: The Risk Of Adverse Effectsmentioning
confidence: 99%
“…Those kinds of changes in expectations for friends were not disturbing, because they were initiated by the partners as accommodations to their changing needs and abilities. But Moremen's (2008a) interviews showed that women aged 55 to 85 years who identified unwanted disruption of their friendship expectations and norms experienced strain in the friendship. For example, discovering that values actually were dissimilar, finding that a friend insisted on having her own way all the time or never reciprocated support, or learning that a friend had betrayed a confidence or told others lies about people or situations all were norm violations that cooled or ended friendships.…”
Section: Expressions Of Cognitive Processes: Thoughts About Friendsmentioning
confidence: 99%